Pediatric rheumatology infusion center: report on therapeutic protocols and infusions given over 4 Years with focus on adverse events over 1 Year - Surabhi S. Vinod; Annelle B. Reed; Jamelle Maxwell; Randy Q. Cron; Matthew L. Stoll (BMC, 2018)
Abstract Background Children with chronic rheumatic disease often require intravenous (IV) therapy. Our center has instituted standardized protocols for use of IV medications in rheumatology patients. Herein, we introduce the therapeutic protocols and report on their short-term safety. Methods This was an institutional review board (IRB) approved retrospective chart review of all patients who had received IV infusions between the years 2012 and 2015 at a single center, prescribed by a pediatric rheumatologist. Infusion medications included abatacept, belimumab, cyclophosphamide, immune globulin, infliximab, methylprednisolone, N-acetylcysteine, pamidronate disodium, rituximab, and tocilizumab. For calendar year 2015, all adverse infusions reactions were recorded along with treatment strategies used to manage them, and outcomes. Rates of adverse events were calculated per infusion medication. Results During calendar years 2012-2015, 7585 IV infusions were administered to 398 unique patients. In the year 2015, 2187 infusions were administered to 224 patients, with 34 patients experiencing 41 infusion reactions (1.9% of all infusions). Rituximab had the highest rate of adverse drug reactions with 10 patients experiencing reactions during 106 infusions (9.4%). None of the reactions were life-threatening, and only 6 resulted in discontinuation of therapy. Conclusions In a recent 4-year span, the UAB Pediatric Rheumatology Infusion Center has given thousands of IV infusions with minimal adverse reactions over a one-year reporting period. The combination of standard infusion protocols, experience of and communication between physicians and nurses who staff the center, and safety of the medications themselves, allows for safe IV administration of a variety of therapies for pediatric rheumatology patients. Trial registration Not applicable; this was a retrospective study.